Develop A Framework of Optimal Spatial Guidelines for Technical Educational Institutions - Nautiyal, Vikas (International Journal of Control and Automation, 2018)
Higher Education Sector in India has been witnessing exceptional development throughout the previous 2-3 decades. There has been a consistent pattern of investment and attention in this area, as shown by the policies of successive administrations and their budget allocations. As a result, a significant portion of the effort to optimize the space should include the ongoing revision of standards. Research aims to solve the situation described above by suggesting ways in which statutory norms for optimal spatial resource planning at universities of technology and architecture should be revised and improved. Inputting the values you want for certain preset input parameters into this recommendation-based matrix system will provide a set of customizable norms.